KONTRIBUSI DUKUNGAN SOSIAL TEMAN SEBAYA TERHADAP SELF REGULATED LEARNING SISWA - M. Iqal Fikri Zalmi; Afrinaldi; Darul Ilmi; Muhiddinnur Kamal (STKIP Subang, 2024)
Learning is an effort made by individuals consciously to produce behavioral changes through activities, practices, and experiences in the interaction of individuals with their environment. Therefore, to achieve learning achievement, students need to have the ability to regulate their learning, namely determining goals for themselves, evaluating their success in achieving goals, and rewarding themselves when they achieve those goals. Peer social support is a significant determinant of students' self-regulated learning. Adolescent students allocate a greater amount of time to socialising with their peers. This study was prompted by an observed phenomenon among students at SMAN 1 V Koto Kampung Dalam, Padang Pariaman Regency. It was noted that some students lacked clear learning objectives, frequently left the classroom during instructional sessions, chose to skip or not attend classes in favour of following their peers, and demonstrated a lack of motivation to prepare for exams. The aim of this study is to evaluate the impact of peer social support on the self-regulation of students at SMAN 1 V Koto Kampung Dalam, Padang Pariaman Regency. This study employs a quantitative research approach with a descriptive correlation design. The study's population comprised students from The study sample comprised eleventh-grade students from SMAN 1 V Koto Kampung Dalam, Padang Pariaman Regency, who were enrolled in the academic year 2023/2024. The sampling method used was proportionate random sampling, which ensured a fair distribution depending on the number of students in each class. The study population comprised 61 individuals. A Likert scale was employed as the instrument for data collection. The data analysis technique employed a fundamental linear regression test. The study results reveal that peer social support (X) has a significant impact on student self-regulated learning (y), accounting for 7.8% of the variance. This is supported by a calculated t value of 2.227, which is higher than the critical t value of 2.001. This demonstrates that for every one-point increment in the peer social support variable, there will be a corresponding rise of 0.078 in the value of self-regulated learning.